Automated Quantitation of CD8-positive T Cells Predicts Prognosis in Colonic Adenocarcinoma With Mucinous, Signet Ring Cell, or Medullary Differentiation Independent of Mismatch Repair Protein Status. (July 2020) - Hartman, Douglas J.; Frank, Madison; Seigh, Lindsey; Choudry, Haroon; Pingpank, James; Holtzman, Matthew; Bartlett, David; Bahary, Nathan; Pantanowitz, Liron; Pai, Reetesh K.
Abstract : Despite their association with DNA mismatch repair (MMR) protein deficiency, colonic adenocarcinomas with mucinous, signet ring cell, or medullary differentiation have not been associated with improved survival compared with conventional adenocarcinomas in most studies. Recent studies indicate that increased T-cell infiltration in the tumor microenvironment has a favorable prognostic effect in colonic adenocarcinoma. However, the prognostic effect of tumor-associated T cells has not been evaluated in histologic subtypes of colonic adenocarcinoma. We evaluated CD8-positive T-cell density in 259 patients with colonic adenocarcinoma, including 113 patients with tumors demonstrating mucinous, signet ring cell, or medullary differentiation, using a validated automated quantitative digital image analysis platform and correlated CD8-positive T-cell density with histopathologic variables, MMR status, molecular alterations, and survival. CD8-positive T-cell densities were significantly higher for MMR protein-deficient tumors ( P <0.001), BRAF V600E mutant tumors ( P =0.004), and tumors with medullary differentiation ( P <0.001) but did not correlate with mucinous or signet ring cell histology ( P >0.05 for both). In the multivariable model of factors predicting disease-free survival, increased CD8-positive T-cell density was associated with improved survival both in the entire cohort (hazard ratio=0.34, 95% confidence interval, 0.15-0.75, P =0.008) and in an analysis of patients with tumors with mucinous, signet ring cell, or medullary differentiation (hazard ratio=0.06, 95% confidence interval, 0.01-0.54, P =0.01). The prognostic effect of CD8-positive T-cell density was independent of tumor stage, MMR status, KRAS mutation, and BRAF mutation. Venous invasion was the only other variable independently associated with survival in both the entire cohort and in patients with tumors with mucinous, signet ring cell, or medullary differentiation. In summary, our results indicate that the prognostic value of MMR protein deficiency is most likely attributed to increased tumor-associated CD8-positive T cells and that automated quantitative CD8 T-cell analysis is a better biomarker of patient survival, particularly in patients with tumors demonstrating mucinous, signet ring cell, or medullary differentiation. Abstract : Supplemental Digital Content is available in the text.